A causal relationship between irritability and cardiovascular diseases: a Mendelian randomization study - Cai, Dihui; Fu, Yin; Song, Yongfei; Lin, Hui; Ba, Yanna; Lian, Jiangfang (Frontiers in Cardiovascular Medicine, 2023)
Background: Observational studies have suggested that irritability are associated with a higher risk of cardiovascular disease (CVD). But the potential causal association is not clear. Therefore, we used Mendelian randomization (MR) analysis to assess the causal association of irritability with CVD risk. Methods: a two-sample MR analysis was performed to confirm the causal association of irritability with the risk of several common CVDs. The exposure data is derived from UK biobank involving 90,282 cases and 232,386 controls and outcome data come from the published genome-wide association studies (GWAS) and FinnGen database. Inverse-variance weighted (IVW), MR-Egger, and weighted median methods were performed to assess the causal association. Furthermore, the mediating effect of smoking, insomnia, and depressed affect was explored by a two-step MR. Results: The MR analysis indicated that several genetically predicted irritability increased the risk of CVD, including coronary artery disease, CAD (OR=2.989; 95% CI=<1.521, 5.874>; p=0.001), myocardial infarction, MI (OR=2.329; 95% CI=<1.145, 4.737>; p=0.020), coronary angiopasty (OR=5.989; 95% CI=<1.696, 21.153>; p=0.005), atrial fibrillation, AF (OR=4.646; 95% CI=<1.268, 17.026>; p=0.02), hypertensive heart disease, HHD (OR=8.203; 95% CI=<1.614, 41.698>; p=0.011), non-ischemic cardiomyopathy, NIC (OR=5.186; 95% CI=<1.994, 13.487>; p=0.001), heart failure, HF (OR=2.253; 95% CI=<1.327, 3.828>; p=0.003), stroke (OR=2.334; 95% CI=<1.270, 4.292>; p=0.006), ischemic stroke, IS (OR=2.249; 95% CI=<1.156, 4.374>; p=0.017), and ischemic stroke of large artery atherosclerosis, ISla(OR=14.326; 95% CI=<2.750, 74.540>; p=0.002). Two-step MR analysis indicated that smoking, insomnia, and depressed affect play important role in the process of irritability leading to cardiovascular disease. Conclusion: our findings support the first genetic evidence of the causality of genetically predicted irritability with the risk of developing into CVDs. Our results deliver a viewpoint that further active intervention to manage an individual’s anger is needed to prevent the occurrence of cardiovascular adverse events. Key word: Mendelian randomization; cardiovascular disease; irritability; coronary artery disease; heart failure.